Effect of db-cAMP on embryonic development of bovine oocytes fertilized with sex sorted semen - Hernández Fonseca, Hugo; Nava Trujillo, Héctor; Sirisathien, Saksiri; Johnson, Lawrence; Guthrie, David; Welch, Glenn; Hernández, Adirmo; Brackett, Benjamin (Revista Científica de la Facultad de Ciencias Veterinarias)
The objective of this study was to improve sexed bovine embryo production with sorted sperm in chemically defined conditions by supplementing the IVF medium with db-cAMP. Cumulus-oocyte complexes (COCs) were matured for 18 h in supplemented TCM-199 and fertilized with X- or Y-bearing sperm in the presence of heparin (10 μg/ml), db-cAMP (1 μM) or no treatment (control). Presumptive zygotes were cultured 54 h in g-SOF. From 72 to 144 h post- insemination (hpi) embryos were cultured in c-SOF+NEA and from 144 to 192 hpi embryos were placed in maturation medium without hormones. No significant differences were found among treatments for Y-sperm when compared to controls. A significant (P menor 0.01) improvement in the proportion of cleaved oocytes was found for X-sperm treated with db-Camp (70.83%) compared to the Y-sperm inseminated oocytes treated wit db-cAMP (46.37%). Treatment with db-cAMP enabled a better (P menor 0.05) blastocyst formation rate (19.29%) compared to control (8.47%) and heparin (10.44%). Treatment of db-cAMP significantly increased the rate of blastocysts in X-sperm inseminated oocytes (30.77%) compared to Y-sperm inseminated oocytes treated the same (9.68%) and compared to X- and Y-sperm treated with heparin (5.88% and 15.15%, respectively) and not treated (9.68% and 7.14%, respectively, P menor 0.05). These results suggest that db-cAMP may prove to be an effective treatment of sorted sperm for in vitro production of female bovine embryos under chemically defined conditions.